EVALUATION OF BARRIERS IN INVENTORY MANAGEMENT OF THE RESTAURANT DELICIAS COZINHA DO MAR USING THE DEMATEL METHOD (ADMPG Journal, 2025)
Effective inventory management strategies are vital, as the availability of the right product, in the right quantity and at the right time, significantly influences purchasing decisions. This research aims to evaluate, using the DEMATEL method, the barriers that exist in the inventory management of the Iguarias Cozinha do Mar Restaurant. It is a family enterprise, managed by one of the family members, who conducts all control of manually. This study used a qualitative methodology with a case study, and bibliographical research and, through the application of the DEMATEL method, prioritized the identified barriers, distinguishing those that exert influence (causes) and directly affect other barriers, from those that are in the group of those influenced (effects) and are influenced by other factors. Finally, a causal diagram is presented that defines the influence relationships between the barriers, aiming to improve the efficiency of the restaurant's inventory management system. It is concluded that seasonal demand interferes with the inventory control process, and the research presented as barriers the susceptibility to internal and external control on the part of the manager, characterized by the installed culture inherent to small family businesses.